2004
DOI: 10.1002/lt.20245
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of histopathologic assessment for the differentiation of recurrent hepatitis C from acute rejection after liver transplantation

Abstract: Histopathologic assessment is considered essential for the differentiation of recurrent hepatitis C (RHC) from acute cellular rejection (ACR) after liver transplantation (LT); however, there is limited information regarding its reliability. The aim of this study was to determine the interobserver and intraobserver agreement of the histopathologic diagnosis of RHC vs. ACR, and to determine the reliability of specific histopathologic features for the differentiation of RHC from ACR. Liver biopsy specimens from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 24 publications
(27 reference statements)
3
86
1
1
Order By: Relevance
“…Although liver biopsy is the most common technique to evaluate both ACR and RHC, the accurate interpretation of liver biopsy samples necessitates skilled and expert LT pathologists, and there may be disagreement even among experienced pathologists. 11 Thus, in practice, it can be difficult to distinguish ACR from RHC histopathologically in HCV-positive transplant recipients. Therefore, there is a need to find novel biomarkers expressed distinctly in ACR to assist in establishing a correct diagnosis.…”
mentioning
confidence: 99%
“…Although liver biopsy is the most common technique to evaluate both ACR and RHC, the accurate interpretation of liver biopsy samples necessitates skilled and expert LT pathologists, and there may be disagreement even among experienced pathologists. 11 Thus, in practice, it can be difficult to distinguish ACR from RHC histopathologically in HCV-positive transplant recipients. Therefore, there is a need to find novel biomarkers expressed distinctly in ACR to assist in establishing a correct diagnosis.…”
mentioning
confidence: 99%
“…As others have noted, 3 the evaluation of a liver allograft biopsy after transplantation from a patient with a history of hepatitis C can be diagnostically challenging. The implications for therapy and possible graft damage with inappropriate treatment require the pathologist and other members of the multidisciplinary transplant team to integrate multiple forms of data when interpreting these types of biopsies.…”
mentioning
confidence: 99%
“…Among them the differentiation from recurrent HCV is difficult especially in the early postoperative period because histologic features overlap 43 , but is critical because the treatment strategy is completely opposite. To date, several studies have evaluated the interobserver agreement for the differential diagnosis of ACR and recurrent hepatitis C. Regev et al 43 evaluatedthe interobserver and intraobserver agreement among five experienced pathologists for the diagnosis of 102 biopsy specimens.…”
Section: Differentiation From Hcv Recurrencementioning
confidence: 99%
“…Among them the differentiation from recurrent HCV is difficult especially in the early postoperative period because histologic features overlap 43 , but is critical because the treatment strategy is completely opposite. To date, several studies have evaluated the interobserver agreement for the differential diagnosis of ACR and recurrent hepatitis C. Regev et al 43 evaluatedthe interobserver and intraobserver agreement among five experienced pathologists for the diagnosis of 102 biopsy specimens. The results indicated that both the interobserver and the intraobserver agreement were relatively low, with Kappa scores ranging from 0.20 to 0.24 for interobserver agreement and from 0.19 to 0.42 for intraobserver agreement, indicating only slight to moderate agreement 43 .…”
Section: Differentiation From Hcv Recurrencementioning
confidence: 99%